Identifikasi Passage Plan Process dengan Risk Assessment Analysis - Zulfa Maulida Nur Hafidzah; Damoyanto Purba; Elly Kusumawati (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This study examines the passage planning process and the application of Risk Assessment Analysis on the MT. Kasim vessel, focusing on the route from Tanjung Gerem to Bengkulu. Through a mixed-method approach, the research identifies and evaluates critical risks in voyage planning. The findings demonstrate that integrating Risk Assessment Analysis into the passage planning process is crucial for enhancing ship safety and operational efficiency. The analysis reveals several key risks, including extreme weather conditions, navigational hazards, and potential technical failures. The study also emphasizes the critical role of the Second Officer in creating the voyage plan, with final oversight and approval from the Captain. In conclusion, the systematic application of Risk Assessment Analysis in passage planning represents a significant best practice in improving maritime safety. Recommendations include regular training, upgrading navigational technology, and developing a comprehensive risk database. This research contributes to a deeper understanding of risk management in the shipping industry and highlights the importance of a proactive approach in ensuring navigational safety.